Evaluation of Polyethylene as Lapped Tape Electrical Insulation for Helium Gas Cooled HTS Power Cables - Manzo E.; Touza W.A.; Bednarz G.; Guvvala N.; Das A.K.; Cheetham P.; Pamidi S.V. (My University, 2025)
Polyethylene (PE) was studied as electrical insulation materials for high temperature superconducting (HTS) power cables using lapped tape electrical insulation design. Gaseous Helium (GHe) cooled HTS cables for electric transport applications were the focus of the study. Electric field distribution was modeled using finite element methods (FEM) for both AC and DC conditions. The partial discharge inception voltage (PDIV) measurements of two test cables were performed under AC and DC conditions at cryogenic temperature. A 3-hour DC soak test was also performed to assess partial discharge behavior under transient DC electric field. The implications of the results were discussed in the context of the electrical insulation system design for GHe-cooled HTS cables in electric transport applications. © 2002-2011 IEEE.